Napovedovanje lastnosti orodnih jekel za delo v vročem stanju pri cikličnem toplotnem obremenjevanju - Markežič, Rok (visokošolska dela, 2020)
High pressure die casting dies, made of hot work tool steels, are during operation exposed to cyclic thermal and mechanical loads. High operational temperatures cause microstructural changes, thermal softening, loss of hardness and consequently reduction in damage and wear resistance. Understanding the loss of hardness of dies during die casting process is crucial for precise die lifetime prediction and prolongation. In this doctoral thesis, first the effect of temperature on the occurrence of damage and wear was researched by examination of a used insert of a die casting die. Numerical methods for temperature fields calculation, hardness measurements, optical microscopy, scanning electron microscopy and x-ray diffraction analysis were used. Results have shown an increase in the occurrence of damage and wear on surfaces with higer temperature during the die casting process. By performing high temperature softening tests, hardness measurements and microstructural analysis, thermal softening of a typical hot work tool steel was analysed. A new model for hardness change predictions during time and temperature dependent conditions was developed on the basis of a known tempering kinetic law and validated. The validation results have shown a good agreement between predicted and measured changes of hardness. The new model was then tested on hardness change predictions during cyclic thermal loading conditions. Cyclic thermal loading tests were performed on a newly developed test equipment. Hardness change predictions with the newly developed model were in good agreement with measured changes of hardness. The use of the new model was additionally demonstrated on hardness change predictions of an insert of a die casting die.
Keywords: Disertacije; dissertations; hardness; high pressure die casting; hot work tool steels; kinetični zakoni popuščanja; microstructure; mikrostruktura; Obraba; Orodja; orodna jekla za delo v vročem stanju; tempering kinetic laws; thermal softening; tlačno litje; toplotno mehčanje; trdota